The effectiveness of Washback for Learning Activities for Vocational Studies: A study of Language Assessment in an Indonesian Polytechnic - Nurul Fadillah (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2017)
Regarding the importance of English for international communication, Indonesian government set up the regulation and included English in the curriculum for schools. English accordingly should be taught from junior high school to university level. Some primary schools in Indonesia even put English as their optional subject beginning in the third year. The regulation may lead to the improvement of human resources especially in education sector because the government believes that will develop national prosperity. In addition, it is also important to improve educational subjects (person who take part in education) for instance teacher, students, academics, etc to maintain the quality in educational sector. The research discusses the effectiveness of using washback to introduce the use of test influences on language teachers and learners activities in the classroom and also examine the concept of washback and language assessment as the instances of the consequential aspect of validity, authentic and direct assessment and difficulty in the test. Keywords: washback, assessment, effectiveness, validity, education, test